ENHANCING ENGLISH SKILLS FOR SHOPKEEPERS: A TAILORED ENGLISH TRAINING MODULE USING ADDIE MODEL - Manalu, Irene Damaian Kristia; Kurniawati, Lemmuela Alvita (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2024)
Based on the results of the needs analysis which revealed the inefficiency in transactions with the foreign customers due to limited English proficiency, this present study aims to develop an English training module for shopkeepers working at showrooms and workshops in the tourist village of Kasongan, Bantul Regency, Yogyakarta, Indonesia. By using the principles of ADDIE (Analysis, Design, Development, Implementation, and Evaluation) instructional design model, the module was developed to hone the shopkeepers’ English skills in serving the foreign customers. Ten participants consisting of 2 showroom and workshop owners as well as 8 shopkeepers participated in this study. Observations and questionnaires were used to gather the data during the needs analysis phase. The data were analyzed and used to design and developed the materials for the module. The present study did not perform the Implementation and Evaluation phases as the 2 phases are going to be done in the subsequent study. This study, therefore, highlights the importance of continuous improvement in the instructional design based on the feedback from both the stakeholders and the target learners in order to ensure the effectiveness of the module..